Terjemah tafsir Jalalain berikut Asbaabun Nuzul - Imam Jalaluddin al_Mahalliy (Sinar Baru, 1990)
ir, Jil.1,c.1-2 ; Jil.3,c.1-2 ; Jil.4,c.1/ir, jil.3,c.3-4/tr, jil.1=c.3-5; jil.2=c.1-5; jil.4=c.2-5/stoc1, jil.1,c.1-5 ; jil.2,c.1-5 ; jil.3,c.1-5 ; jil.4,c.1-5